Wakaf Uang untuk Optimalisasi Pembiayaan Usaha Mikro Kecil dan Menengah (UMKM) Melalui Koperasi Syariah di Indonesia - Ayi Puspita Fajariah; Sudana Sudana; Aam Rusydiana (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
Waqf is one of the Islamic law that concern people’s lives which is has a function for the community interest to obey to Allah SWT. In practice, waqf in Indonesia faces many hard problems, because commonly known as non-productive waqf. This research is aim to identify the priority factors that being a barrier to develop the practice of cash waqf on Small Medium Enterprises (SME) financing through Islamic Cooperation in Indonesia using Analytic Network Process (ANP) method.  The result shows that the problems appeared in managing cash waqf in Indonesia divided into two important aspects; there is an internal and external aspect. The rank for most priority problems in inner aspect to less priority based on the priority result is the accountability aspect, human resources, and institutional challenge. The position for external issues based on the priority result is authority aspect and public aspect.